The cotton swab method: an accurate and less invasive way to assess fecal consistency in weaned pigs - Esben Østergaard Eriksen; Martin Friis Sejersen; Ken Steen Pedersen (BMC Veterinary Research, 2024)
Abstract Background Researchers and pig veterinarians are interested in assessing pigs’ fecal consistency. This study developed a standardized protocol and scale for the cotton swab method, which is a way of assessing the fecal consistency in pigs. The accuracy of the cotton swab method was evaluated in weaned pigs using fecal dry-matter analysis as a golden standard. The study also proposed fecal dry-matter percentage thresholds for the categorization of fecal consistency on a four-point scale. Results The thresholds of 10.3%, 16.6%, and 21.9% fecal dry-matter were suggested for categorization of the consistency of fecal samples on a four-point scale. The accuracy of the cotton swab method was high. The agreement to the four-point fecal consistency score derived from the fecal dry-matter percentage was almost perfect (weighted Gwet’s agreement coefficient = 0.87 [95% confidence interval: 0.84; 0.91]). The cotton swab method had a sensitivity of 85.0% (95% confidence interval: 76.5; 91.4) and a specificity of 95.2% (95% confidence interval: 92.0; 97.3) when used to diagnose whether pigs had diarrhea or not. For non-diarrheic pigs, the method almost always (n = 287/289) required less handling than the collection of a fecal sample by digital rectal manipulation. Conclusion The cotton swab method is an accurate way to assess fecal consistency in pigs, both on a four-point scale and as a dichotomous diarrhea score. The method is quick to perform and less invasive than methods relying on the collection of fecal samples. New fecal dry-matter thresholds between feces of different consistencies were proposed.